PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA PADA MATERI PECAHAN KELAS V SEKOLAH DASAR - Ni Wayan Nera Wati; Ni Wayan Jupita; Ni Made Rita Dwi Cahyani; I Made Sujana Adnyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve fifth-grade elementary school students’ mathematics learning outcomes on fraction material through the implementation of the Problem Based Learning model. This study used Classroom Action Research conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects of the study were 30 fifth-grade elementary school students. Data collection techniques included tests, observation, and documentation. The data were analyzed using descriptive quantitative analysis techniques by calculating the average score and percentage of learning completeness. The results showed that the implementation of Problem Based Learning improved students’ mathematics learning outcomes, learning activities, and student participation during the learning process. The average score increased from 70 in cycle I to 84 in cycle II, while learning completeness increased from 63% to 90%. Therefore, the Problem Based Learning model is effective in improving students’ mathematics learning outcomes on fraction material.